WAGE DIFFERENTIALS BETWEEN THE PUBLIC AND PRIVATE SECTORS IN INDIA - Elena Glinskaya and Michael Lokshin (World Bank Policy Research Working Paper 3574, April 2005, 2005)
This study uses 1993-94 and 1999-2000 India Employment and Unemployment surveys to investigate wage differentials between the public and private sectors as well as workers' decisions to join a particular sector. To obtain robust estimates of the wage differential, we apply three econometric techniques each relying on a different set of assumptions about the process of job selection. All three methods show that differences in wages between public sector workers and workers in the formal-private and informal-casual sectors are positive and high. Estimates show that, on average, the public sector premium ranges between 62 per cent and 102 per cent over the private-formal sector, and between 164 per cent and 259 per cent over the informal-casual sector, depending on the choice of methodology. Our review of wage differentials (estimated using similar methodologies) across the world shows that India has one of the largest differentials between wages of public workers and workers in the formal private sector. The wage differentials in India tend to be higher in rural as compared to urban areas, and are higher among women than among men. The wage differential also tends to be higher for low-skilled workers. There is considerable evidence of an increase in the wage differential between 1993-1994 and 1999-2000.